PENDAMPINGAN PERENCANAAN PEMBELAJARAN BAGI SEKOLAH PENGGERAK DI SD MUHAMMADIYAH 1 MENGANTI - Nanang Khoirul Umam; Anantama Dewantoro (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2022)
Since the launch of the Independent Learning Campus Merdeka Program, the Ministry of Education and Culture has made a number of breakthroughs in socialization, training, education and training, technical guidance and coaching. However, at the implementation level, not all projects went according to plan due to various problems identified. Among them are technical issues such as the development of the operational curriculum of the education unit, the development of learning modules, the differentiation of learning and study programs. The team's solution to this problem was to help educators and principals. The implementation steps are to provide assistance and workshops. As a result of this activity, educators have gained new insights in developing assessment tools for driving schools. After this activity, it is recommended that a follow-up plan related to the guidelines in the lesson plan need to be developed